Transmission-Blocking Strategies Against Malaria Parasites During Their Mosquito Stages - Yu, Shasha; Wang, Jing; Luo, Xue; Zheng, Hong; Wang, Luhan; Yang, Xuesen; Wang, Ying (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria is still the most widespread parasitic disease and causes the most infections globally. Owing to improvements in sanitary conditions and various intervention measures, including the use of antimalarial drugs, the malaria epidemic in many regions of the world has improved significantly in the past 10 years. However, people living in certain underdeveloped areas are still under threat. Even in some well-controlled areas, the decline in malaria infection rates has stagnated or the rates have rebounded because of the emergence and spread of drug-resistant malaria parasites. Thus, new malaria control methods must be developed. As the spread of the Plasmodium parasite is dependent on the part of its life cycle that occurs in mosquitoes, to eliminate the possibility of malaria infections, transmission-blocking strategies against the mosquito stage should be the first choice. In fact, after the gametocyte enters the mosquito body, it undergoes a series of transformation processes over a short period, thus providing numerous potential blocking targets. Many research groups have carried out studies based on targeting the blocking of transmission during the mosquito phase and have achieved excellent results. Meanwhile, the direct killing of mosquitoes could also significantly reduce the probability of malaria infections. Microorganisms that display complex interactions with Plasmodium, such as Wolbachia and gut flora, have shown observable transmission-blocking potential. These could be used as a biological control strategy and play an important part in blocking the transmission of malaria.